Modelling alicyclobacillus acidoterrestris inactivation in apple juice using thermosonication treatments - Tremarin, Andréia (2019)
A spore-forming bacterium, Alicyclobacillus acidoterrestris, is often responsible for fruit juices quality degradation. The objective was to study the influence of ultrasounds and combinations with temperature (thermosonication) on A. acidoterrestris spores inactivation in apple juices. Commercially available juice was artificially inoculated with the bacterium (∼105 CFU/mL). Sonication was carried out in an ultrasonic bath (35 kHz; 120–480 W) at room temperature and at 70, 80, 85, 90 and 95 °C for different times. Thermal treatments at the same temperatures were performed as a control. Sonication had no significant effect on A. acidoterrestris spores inactivation. However, when applied at 70 and 80 °C, it allowed 1 log-cycle more of inactivation when compared to thermal treatments and at the end of the processes. Ultrasounds at higher temperatures required approximately half of the treatment time to attain the same inactivation that occurred when the thermal processes were applied alone. In thermosonicated juices, spores decreased by 4.8, 4.7 and 5.5 log-cycles (at 85, 90 and 95 °C, respectively) after 90, 60 and 20 min. The Weibull model satisfactorily fitted inactivation data of thermosonicated juices. Thermosonication is efficient for A. acidoterrestris spores inactivation, with a drastic impact on spores’ loads when high temperatures are used.